Invocation Receptivity in Female of Rabbit - Martin Fik; Cyril Hrnčár; Henrieta Arpášová; Jozef Gašparík (Scientific Papers Animal Science and Biotechnologies, 2023)
The target of this work was verified effect of transport females in the car for advance state of receptivity in young females broiler rabbits. We used nulliparous females of broiler hybrid HYCOLE (age 4-5 months, weight 3.5-3.8 kg). Experiment was realized twice, initially in half of November (31 females), after that in half of February (32 females). Females were laid individually in boxes, after they were transported by car 1 hour (50 km). Before and after experiment we detected state of receptivity in females with coloration of vulva. The state of receptivity was determined from 1 for 4 colour of vulva. (1 – anaemic coloration of vulva, 2- pink, 3 – red, 4- violet). We detected positive state of transport, on the receptivity. In November before transport was average of receptivity 1.87, after transport 2.25. The state of receptivity will be improved in 12 females (38.71 %). Improve from 1 to 2 was detected in 4 females, from 2 to 3 in 8 females. Improved from 2 to 4, or from 3 to 4 wasn´t noticed in this group. The state of receptivity wasn´t changed in 19 females (61.29 %). In the state of receptivity 1 stayed 2 females, in the state 2 stayed 15 females, in the state 3 stayed 2 females and in the state 4 wasn´t any female. In February after the end of experiment, state of receptivity was improved with transport in the car from 2.19 to 2.65. The state of receptivity was improved in 13 females (40.63 %).  Improve from 1 to 2 we detected in 1 female, from 2 to 3 we detected in 8 females, from 2 to 4 we detected in 2 females, from 3 to 4 in 2 females. In 19 females (59.38%) we don´t noticed change state of receptivity. In the state of receptivity 1 were 2 females, in 2 were 11 females, in 3 were 5 females, and in 4 was 1 female.